Efficacy and Safety of Intralesional Vitamin D3 Injection in Recalcitrant Periungual Warts: A Randomized Controlled Trial (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Although the treatment of recalcitrant warts is often disappointing due to its high recurrence rates, the intralesional injections of Vitamin D3 (as an immunotherapeutic molecule) may regulate epidermal cell proliferation.Objective: To evaluate whether intralesional vitamin D3 immunotherapy is efficient and secure in treating the recalcitrant periungual warts.Materials and Methods: This randomized controlled therapeutic trial was performed in the Department of Dermatology and Venereology of Combined Military Hospital, Dhaka from July 2018 to December 2019. A total of 64 participants’ having different sizes and duration of recalcitrant periungual warts were included. Half of them were injected with about 0.2ml vitamin D3 solution (600,000 IU, 15 mg/ml) at the base of the wart (Group-A) and the remaining participants were subjected to cryotherapy (Group-B). A follow-up period of 6 months following the last session was performed to detect any recurrence.Results: The mean age of participants in Group A and B were 25.9±12.6 and 26.4±12.4 years, respectively (78.1% male in Group-A and 62.5% in Group B). The size and duration of warts between the two groups were not statistically significant (p>0.05). The treatment outcome in Group-A varied from excellent 19(59.4%) to significant 8(25.0%), moderate 3(9.4%), mild (3.1%), and no response 1(3.1%), whereas in Group-B, the results were as follows: excellent 13(40.6%), significant 3(9.4%), moderate 9(28.1%), mild 7(21.9%). The efficacy was significantly higher in Group-A when compared to Group-B (p